2020
DOI: 10.1002/ppul.24679
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen insecurity and mortality in resource‐constrained healthcare facilities in rural Kenya

Abstract: Introduction Pneumonia is the leading cause of death globally in children. Supplemental oxygen reduces mortality but is not available in many low‐resource settings. Inadequate power supply to drive oxygen concentrators is a major contributor to this failure. The objectives of our study were to (a) assess the availability of therapeutic oxygen; (b) evaluate the reliability of the electrical supply; and (c) investigate the effects of suboptimal oxygen delivery on patient outcomes in selected healthcare facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Lower access to intensive care, and particularly to oxygen, may reduce recovery rates for severe cases in Uganda and more broadly in this region in DALYs lost and mortality. 37,38 We also make no adjustments for the impact of age structure on underlying transmission, but compare the age-based predicted mortality for a hypothetical equivalent transmission uniformly across each age-group. To address these uncertainties, this article has taken a conservative approach to comparing COVID-19 impact with that of lockdown-related program deterioration, assuming a very high transmission of COVID-19 (a 20% detectable infection rate) across Uganda.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower access to intensive care, and particularly to oxygen, may reduce recovery rates for severe cases in Uganda and more broadly in this region in DALYs lost and mortality. 37,38 We also make no adjustments for the impact of age structure on underlying transmission, but compare the age-based predicted mortality for a hypothetical equivalent transmission uniformly across each age-group. To address these uncertainties, this article has taken a conservative approach to comparing COVID-19 impact with that of lockdown-related program deterioration, assuming a very high transmission of COVID-19 (a 20% detectable infection rate) across Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…Lower access to intensive care, and particularly to oxygen, may reduce recovery rates for severe cases in Uganda and more broadly in this region in DALYs lost and mortality. 37 , 38 We also make no adjustments for the impact of age structure on underlying transmission, but compare the age-based predicted mortality for a hypothetical equivalent transmission uniformly across each age-group.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have reported similar findings in Kenya, Uganda, Papua New Guinea, and other African and Asia-Pacific contexts. [7][8][9][10][11] Indeed, unreliable oxygen supplies and deficiencies in oxygen use are consistent and persisting problems for many hospitals in these regions, particularly in rural and remote settings.…”
Section: Challenges In Oxygen Accessmentioning
confidence: 99%
“…These surveys showed a lack of basic equipment such as pulse oximeters and oxygen delivery systems, eg, cylinders or concentrators. Availability of oxygen delivery systems ranged from 42%-94% between facilities, with wide variability in the consistency of availability [ 13 - 15 , 18 , 20 , 22 , 24 , 25 , 28 , 30 , 33 ]. For example, the highest reported availability was in a study of private and public facilities in Uganda which showed that 15 of 16 facilities had access to oxygen at least half of the time.…”
Section: Resultsmentioning
confidence: 99%